Photo-assisted catalytic degradation of acetaminophen using peroxymonosulfate decomposed by magnetic carbon heterojunction catalyst. (October 2019) - Noorisepehr, Mohammad; Ghadirinejad, Khashayar; Kakavandi, Babak; Ramazanpour Esfahani, Amirhosein; Asadi, Anvar
Abstract: Catalytic oxidative degradation of acetaminophen (ACT) was evaluated using magnetic mesoporous carbon (MNPs@C) coupled with UV light and peroxymonosulfate (PMS). The performance of hybrid system (i.e., MNPs@C/UV/PMS) was assessed as a function of some operational factors (e.g., reaction time and different concentrations of catalyst, PMS and ACT) in a batch system. MNPs@C represented a high magnetic response and was easily recovered from aqueous solution via an external magnet. A significant synergistic effect was observed among the applied techniques in MNPs@C/UV/PMS system for ACT degradation. After 40 min reaction, the removal efficiencies of 97.4 and 63.5% were obtained for ACT and TOC, respectively. Both adsorption and oxidation mechanisms were responsible simultaneously for ACT removal in MNPs@C/UV/PMS system. Under optimum conditions, the removal rates of ACT and TOC were reduced slightly to 91.7 and 49.4% after five consecutive catalyst uses, which indicates the excellent reusing potential of MNPs@C. In addition, a high stability was detected for as-prepared catalyst during recycling tests, since the quantity of leached Fe was <0.2 mg/L. Methanol and tert -butyl alcohol showed a strong quenching effect on the performance of MNPs@C/UV/PMS system, demonstrating the dominant role of SO4 - and HO radicals in ACT degradation process. MNPs@C in comparison with ferrous ions, as a homogeneous catalyst, showed a better performance in the activation of PMS and ACT degradation. Integration of MNPs@C, UV and PMS exhibited an excellent performance into ACT removal over 40 min reaction, which can be utilized as an effective and promising technique for the efficient decontamination of polluted waters. Graphical abstract: Image 1 Highlights: A heterojunction catalyst coupled with UV was used for activating PMS and ACT degradation. A tentative mechanism was proposed for PMS activation and reactive species generation. MNPs@C showed better performance towards PMS activation compared to ferrous ions. Over 97% and 63% of ACT and TOC removed by MNPs@C/UV/PMS system at optimum conditions, respectively.